Energy transition: Financial participation and preferred design elements of German citizens - Barbara Breitschopf; Uta Burghard (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2023)
This paper investigates the relation between financial participation and preferences for design elements as well as attitudes towards the energy transition. The design elements are used to characterise dimensions of the energy transition. Based on a survey of more than 1000 German citizens, we find significant differences in attitudes and preferences for design elements of the energy transition between respondents who financially participate and those that do not. We further learn that energy justice is important, but is less supported in case that subsidies of disadvantaged consumers lead to higher burdens for the remaining society.
Keywords: 330; Energy transition; Financial participation; Preferences; Design elements; Dimensions; Socio-demographic factors